Pacing, packing and sex-based differences in Olympic and IAAF World Championship marathons? - Hanley, B. (Journal of Sports Sciences, 2016)
The aim of this study was to describe pacing profiles and packing behaviours of athletes in Olympic and World Championship marathons. Finishing and split times were collated for 673 men and 549 women across nine competitions. The mean speeds for each intermediate 5 km and end 2.2 km segments were calculated. Medallists of both sexes maintained even-paced running from 10 km onwards whereas slower finishers dropped off the lead pack at approximately half-distance. Athletes who ran with the same opponents throughout slowed the least in the second half (P < 0.001, men: ES = 1.19; women: ES = 1.06), whereas other strategies such as moving between packs or running alone were less successful. Overall, women slowed less (P < 0.001, ES = 0.44) and were more likely to run a negative split (P < 0.001), and their more conservative start meant fewer women dropped out (P < 0.001). This also meant that women medallists sped up in the final 2.2 km, which might have decided the medal positions. Marathon runners are advised to identify rivals with similar abilities and ambitions to run alongside provided they start conservatively. Coaches should note important sex-based differences in tactics adopted and design training programmes accordingly.